Moralitas dan kesadaran terhadap kepatuhan wajib pajak UMKM dengan memanfaatkan fasilitas perpajakan dimasa pandemi Covid-19 - Sularsih, Hermi; Wikardojo, Soko (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This research aims to determine the effect of morality and awareness on MSME taxpayer compliance. Based on the data obtained in Gempol District, there are 400 MSMEs. The sample is a collection of subjects that represent the population. The sampling technique used was the purposive sampling method with several criteria: 1) The business is engaged in manufacturing. 2) A business that has been around for more than 5 years. 3) MSMEs that have NPWP. Based on the criteria in determining the number of samples of 255 MSMEs that meet the criteria. So that in this case, the number of samples in the study amounted to 255 MSMEs. Multiple regression analysis tests using SPSS. The results of the study state that significantly the morality variable has a positive effect on MSME taxpayer compliance and awareness variables also affect the compliance of MSME taxpayers. Â